Elucidating the synergistic fabrication of dual embedded (χ-Fe5C2 + θ-Fe3C) carbide nanocomposites in Na-FeCa@AC/HZSM-5 integrated catalyst for syngas conversion to aromatics. (15th September 2022) - Nawaz, Muhammad Asif; Saif, Maria; Li, Minzhe; Song, Guiyao; Zihao, Wang; Chen, Chonghao; Liu, Dianhua
Graphical abstract: The highly dispersed Fe3 O4 nanocrystals embedded in a carbon matrix, triggered the extent of CO chemisorption that significantly provoked the (54%χ-Fe5 C2  + 44%θ-Fe3 C) carbide nanoparticles, and potentially deflected the deactivation manners by spatial confinement of Fe@AC species in defective graphite patches, achieving 60% aromatics selectivity in 97% CO conversion. Highlights: Fabricating the highly dispersed Fe3 O4 nanocrystals embedded in a carbon matrix of defective graphite sheet. Triggering the extent of CO chemisorption on highly tuned Fe 0 surface that significantly provoked the carburization behavior. Yielding high purity (98%) dually embedded (χ-Fe5 C2  + θ-Fe3 C) nano particles via the effective melioration of surface carbon reactions. Potentially deflecting the deactivation manners by spatial confinement of Fe@AC species in defective graphite patches. Achieving 97% CO conversion and 60% aromatics selectivity with the enrichment of carbide species during reaction. Abstract: Herein, an activated carbon (AC) modified Fe-oxide catalyst has been employed in Na-FeCa@AC/HZSM-5 integrated catalytic system for the direct conversion of syngas to aromatics (STA). In comparison to the conventionally impregnated Fe/C catalysts, the spatial confinement of highly dispersed Fe3 O4 nanocrystals in a rigid geometry of defective graphite sheet by the efficient modulation of different (AC, Ca) promoters, calcination environment and the surface carbon reactions in sol-precipitation method, potentially deflected the sintering and agglomeration behavior of Fe nanoparticles. The meliorated higher extent of CO chemisorption on the tuned Fe surface and the different reduction/carburization schemes cultivated the high-purity (54% χ-Fe5 C2  + 44% θ-Fe3 C) carbide nanoparticles. The encapsulation of perforated carbon patches during carburization favored the stabilization of highly active carbide phase under reaction conditions, where the subsequent precipitation of carbon elements led to the further recruitment of multi-layer carbide films for the accelerated CO dissociation and the partial decomposition of olefinic intermediates. Since, the dually embedded terrace carbide islands were rather enriched from one phase to another (27.3%θ-Fe3 C ⇌ 70.7%χ-Fe5 C2 ) during the reaction, giving a simultaneously enhanced catalytic activity of 97% CO conversion and 60% aromatics selectivity while suppressing the net CO2 release (21%). The current study anticipates a promising scheme to formulize a highly active and stable iron-based catalyst to be integrated with HZSM-5 for STA process.